Freeze-Drying Improved the Stability of Tuberculin Purified Protein Derivative (PPD) in Mammals - Zavhorodnii , Andrii; Bilushko , Viktor; Paliy, Anatoliy; Kalashnyk , Mykola; Kalashnyk , Natalia; Paliy, Andriy (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(1): 063–067